The Absorptive Capacity of Fatwa Institutions in Indonesia on Contemporary Issues - Subli, Mohamad; Salenda, Kasjim; HL, Rahmatiah; Rahman, Sainul (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2024)
The existence of fatwa institutions is very important because it can provide a roadmap for resolving contemporary legal problems. This research aims to examine the nature and importance of fatwas, the existence of fatwa institutions in Indonesia and their mandate and the absorption capacity of fatwa institutions in Indonesia in responding to current problems. Research was carried out in the literature using a normative-historical approach in analyzing the absorption capacity of fatwa institutions in responding to contemporary issues. The fatwa institutions in question are centered on the Majlis Tarjih Muhammadiyah, Bahtsul Masa'il Nahdlatul Ulama (NU) and by fatwa institutions such as the Indonesian Ulema Council (MUI). The results show that a fatwa is a form of answer from a mufti to a question asked by a mustafti which is based on a compelling case. Remembering that the mufti is the person chosen to be the caliph and successor of the Prophet, as stated by Imam Syatibi. Therefore, fatwas have a strategic and important position in social life to answer contemporary problems. Fatwa plays an important role in answering contemporary problems, especially problems in the era of modernization. One reason is because the majority of Muslims need legal answers that can solve problems. Based on the number of fatwas that have been issued, it shows that fatwa institutions in Indonesia have responded to contemporary legal issues.